2017
DOI: 10.1002/14651858.cd004479.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Simple aspiration versus intercostal tube drainage for primary spontaneous pneumothorax in adults

Abstract: Available trials showed low to moderate-quality evidence that intercostal tube drainage produced higher rates of immediate success, while simple aspiration resulted in a shorter duration of hospitalization. Although adverse events were reported more commonly for patients treated with tube drainage, the low quality of the evidence warrants caution in interpreting these findings. Similarly, although this review observed no differences between groups when early failure rate, one-year success rate, or hospital adm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
2
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 55 publications
(79 reference statements)
1
30
2
2
Order By: Relevance
“…Several randomized studies have shown that simple needle aspiration (NA) reduces the hospital length of stay without increasing the recurrence rate of pneumothorax . A recent Cochrane systematic review (2017) also reported a shorter hospital stay and a reduction of side effects after simple NA compared to chest tube drainage (CTD) . Another review of well‐conducted randomized studies published the same year and including results of the largest study in this field by Thelle et al came to the same conclusions .…”
Section: Manual Aspiration or Chest Tube Insertion?mentioning
confidence: 75%
“…Several randomized studies have shown that simple needle aspiration (NA) reduces the hospital length of stay without increasing the recurrence rate of pneumothorax . A recent Cochrane systematic review (2017) also reported a shorter hospital stay and a reduction of side effects after simple NA compared to chest tube drainage (CTD) . Another review of well‐conducted randomized studies published the same year and including results of the largest study in this field by Thelle et al came to the same conclusions .…”
Section: Manual Aspiration or Chest Tube Insertion?mentioning
confidence: 75%
“…There were insufficient numbers of studies included to determine if the choice of medical interventions (needle aspiration versus ICD) for PSP influenced recurrence rates. A recent meta-analysis comparing RCTs of needle aspiration versus ICD insertion found no difference of recurrence at 1 year between the interventions [49]. There were no randomised data comparing conservative management to needle GANESALINGAM [9] HUANG [24] KIM [26] NOH [33] OLESEN [6] SADIKOT [4] Overall AL-ALAWI [17] GANESALINGAM [9] MEHTA [31] NOH [33] OUANES-BESBES [13] SADIKOT [4] TAN [5] Overall Favours male recurrence Favours female recurrence FIGURE 3 Meta-analysis of odds ratios for primary spontaneous pneumothorax recurrence in males versus females from seven observational studies.…”
Section: Discussionmentioning
confidence: 99%
“…Both procedures have been examined in several prospective randomized studies [34,104,[106][107][108], systematic review articles [109,111,113], and meta-analyses [110,113]. In a current Cochrane Review [117] of 6 RCTs, the primary treatment method (needle aspiration or small-lumen chest drain) showed a better primary success rate of drain application, while the hospitalization time following aspiration is shorter. There were no significant differences in the hospitaliza- tion rate, the recurrence rate after 1 year, or in patient satisfaction.…”
Section: Literature: Consensus Of Expertsmentioning
confidence: 99%